Want this question answered?
Be notified when an answer is posted
0
6xy(2x2 - 3y)
5xy+4=9 is the problem, right? 5xy+4=9. Now subtract the 4 from both sides. 5xy=5. Ok, then, that looks less scary. Now, divide both sides by 5, to get xy=1. Hmm, a lot simpler. Now, divide both sides by x to get y by itself. So, y=1/x. Alright. That's your line! No, its not a straight line. There is a vertical asymptote where x=0, and the two segments aren't straight. But that's a simpler form of the equation. Hope that helped!
If:xy = x2 + y2 + 2xyThen:x2 + xy + y2 = 0Do you want to solve it for x?x2 + xy + (y/2)2 = (y/2)2 - y2(x + y/2)2 = y2/4 - y2x + y/2 = ± √(-3y2/4)x = -y/2 ± y√(-3) / 2x = (-y ± yi√3) / 2
Assuming the two equations are: 3xy - 3 = 0 ............................................. 1 2xy = 0 ............................................. 2 Then from eq 1 xy = 1 from eq 2 xy = 0 That is not possible. Or, assuming the equation is 3xy - 3 + 2xy = 0 Then 5xy = 3 or y = 3/5x Substitute for any value of x to get the value of y
(2x - 3y)(x + y)
(-5xy):(-xy)=
xy(7+2y-3x)-6xy
3, since the degree of a polynomial is equivalent to its highest power.
1xy
The coefficient of xy is the number that multiplies the product of x and y in a given expression. For example, in the expression 5xy, the coefficient of xy is 5.
0
If x - 3y = 12, we can solve for x in terms of y: x = 12 + 3y. Then, to find xy, we multiply x by y: xy = y(12+3y) = 12y + 3y^2.
(x - 1)(2x + y)
2/y
4
6xy(2x2 - 3y)